2023
DOI: 10.1039/d2ta08244f
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced ion conductivity of “water-in-salt” electrolytes by nanochannel membranes

Abstract: Understanding ion transport in electrolytes is fundamentally significant in nanofluidic, energy and environmental sciences. Enhanced ion transport is widely observed in dilute electrolytes confined in nanochannels, but in concentrated electrolytes...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…The stratification reduces ion dragging and crowding and allows more rapid ion diffusion throughout the nanochannel. 35,36…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The stratification reduces ion dragging and crowding and allows more rapid ion diffusion throughout the nanochannel. 35,36…”
Section: Resultsmentioning
confidence: 99%
“…The stratification reduces ion dragging and crowding and allows more rapid ion diffusion throughout the nanochannel. 35,36 To demonstrate the advantage of using porous MOF membranes as potential electrolytes, we compared their ion-conducting performance with that of graphene oxide (GO) membrane-based system, which is often used as a classical benchmark material. It can be clearly seen that GO-DES6 also demonstrated greatly enhanced conductivity (24.17 mS cm −1 ), further confirming the promotive role of nanoconfinement in ion transport (Fig.…”
Section: Ionic Conductivity Behavior Of the Nanoconfined Desmentioning
confidence: 99%
“…Ionic liquids (ILs) have high ionic conductivity, low vapor pressure, and excellent thermal stability, making them ideal candidates for energy storage, catalysis, and electrochemistry. However, one of the major challenges to restricting the wide use of ILs is their low ionic conductivity at low temperatures. Such low ionic conductivity of pure ILs is often due to their high viscosity and low diffusivity. ,, Our recent work found that the nanoconfinement effect of ILs within 2D materials can overcome these limitations by increasing the effective concentration of ions and reducing their mobility restrictions, thus enhancing ionic conductivity. , The nanoconfined effect is a phenomenon where the confinement of material in a nanostructure leads to changes in its properties due to the interaction between the material and the nanostructure. The confinement of ILs results in several interesting effects, including increased density, increased ionic conductivity, and enhanced ion-pairing and structural ordering. These effects are a direct result of the strong electrostatic interactions between the charged ions and the charged surfaces of the nanochannel.…”
Section: Introductionmentioning
confidence: 99%
“…2,5,6 Our recent work found that the nanoconfinement effect of ILs within 2D materials can overcome these limitations by increasing the effective concentration of ions and reducing their mobility restrictions, thus enhancing ionic conductivity. 7,8 The nanoconfined effect is a phenomenon where the confinement of material in a nanostructure leads to changes in its properties due to the interaction between the material and the nanostructure. 7−14 The confinement of ILs results in several interesting effects, including increased density, increased ionic conductivity, and enhanced ion-pairing and structural ordering.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Current research has focused on the ionic conductivity, structural heterogeneity, and interaction between the electrolyte and solid surface which leads to the formation of a solid-electrolyteinterphase in bulk aqueous solutions of lithium salts. Recently, Peng and Ye et al [9] discovered that 21-mol/kg LiTFSI solution confined in two-dimensional (2D) graphene oxide (GO) nanochannels demonstrated a quadrupled ionic conductivity in comparison to bulk solutions. This observation suggests that a layered structure is formed within the confinement condition, where a free anion layer moves between two continuous water-cation layers, resulting in a significant increase in ionic transport.…”
Section: Introductionmentioning
confidence: 99%